PENALARAN ANALOGI MATEMATIS PADA MATERI SEGI EMPAT DAN SEGITIGA DITINJAU DARI KECERDASAN EMOSIONAL SISWA - Tuti, Isma Wati; Halini, Halini; Ahmad BS, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aim to investigate analysis mathematics analogy on rectangular and triangle material that are viewed based on the level of students? emotional intelligence. Research method which is used in investigating the research is descriptive method in form of survey research. The subject of research is students class VIII B of MTs TI AL-Madani Pontianak and the object the research is mathematic analogy analysis on rectangular and triangle material that are viewed based on the level of students? emotional intellegence. The number of students the are become the research subject are 21 students. The selection of students to be the research subject is based on the teacher recommedation. The result of data analysis shows that students who have high level of emotional intellegence, the result of analytical reasoning tests as a whole are high, but the analytical stage are high, moderate, and low. Students who have moderate level of emotional intellegence, the result of analytical reasoning tests as a whole are moderate, but the analytical stage are high, moderate, and low. Students who have low level of emotional intellegence, the test result as a whole and analytical stages are low. Keywords: Reasoning Mathematical Analogy, Rectangular and Triangle, and Emotional Intellegence.